Pengaruh Supervisi Kepala Sekolah Terhadap Kinerja Guru SMA - Aprianto, Nof (Journal of Innovation in Teaching and Instructional Media, 2024)
This study aims to determine the effect of principal’s supervision on the performance of teachers in SMA Negeri 1 Banyuasin II. The method used in this study is a quantitative which contains two variables, principal’s supervision (X1) and teacher’s performance (Y). Data were obtained through a questionnaire distributed to teachers at SMA Negeri 1 Banyuasin II and analyzed using simple linear regression statistical techniques. The results showed that supervision carried out by the school’s principal has a significant influence on teacher’s performance. Effective supervision, including aspects of monitoring, evaluation and guidance, has been proven to be able to improve the quality of teaching and teacher’s professionalism. These findings indicate that the active role of school’s principals in carrying out supervision is very important to support improvements in teacher’s performance and, ultimately, the quality of education in the school. This study recommends that school’s principals intensify constructive and sustainable supervision activities to create an optimal learning environment.